System of criteria and requirements that determine rolling stock velocities along railroad switches - B. E. Gluzberg (Вестник Научно-исследовательского института железнодорожного транспорта, 2023)
Introduction. Railroad switches velocities significantly affect line throughput capacity. The article examines approaches to establishing railroad switches velocities in connection with intensified traffic, new designs of rolling stock, organisation of fast, high-speed and heavy traffic.Materials and methods. Railroad switches velocities are determined by safety criteria and traffic intensity. The researcher analysed the criteria for railroad switches velocities design, railroad switches velocities for particular types of the rolling stock, velocities along railroad switches combinations. The author examined methods for establishing velocities along rail-road switches in curved sections of the track.Results. The article provided data on speed limits on railroad switches considering their actual condition and presented railroad switches test results substantiating the speed criteria in use.Discussion and conclusion. These criteria, requirements and methods for establishing rolling stock railroad switches velocities constitute a unified system for developing railroad switches, establishing and limiting the rolling stock railroad switches velocities under operating conditions.